2018
DOI: 10.1186/s13059-018-1406-4
|View full text |Cite
|
Sign up to set email alerts
|

Observation weights unlock bulk RNA-seq tools for zero inflation and single-cell applications

Abstract: Dropout events in single-cell RNA sequencing (scRNA-seq) cause many transcripts to go undetected and induce an excess of zero read counts, leading to power issues in differential expression (DE) analysis. This has triggered the development of bespoke scRNA-seq DE methods to cope with zero inflation. Recent evaluations, however, have shown that dedicated scRNA-seq tools provide no advantage compared to traditional bulk RNA-seq tools. We introduce a weighting strategy, based on a zero-inflated negative binomial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
188
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 66 publications
(4 reference statements)
0
188
0
Order By: Relevance
“…Yet, a recent, large-scale comparison study of DE analysis has suggested that bulk DE testing packages perform comparably to the best-performing single-cell tools . Furthermore, when bulk tools are adapted to model single-cell data via introducing gene weights into the tests, these tools have been suggested to outperform their single-cell counterparts (Van den Berge et al, 2018). According to this comparison, the top-performing DE analysis tools are DESeq2 (Love et al, 2014) and EdgeR (Robinson et al, 2010) in combination with weights estimated by ZINB-wave .…”
Section: Differential Expression Testingmentioning
confidence: 99%
“…Yet, a recent, large-scale comparison study of DE analysis has suggested that bulk DE testing packages perform comparably to the best-performing single-cell tools . Furthermore, when bulk tools are adapted to model single-cell data via introducing gene weights into the tests, these tools have been suggested to outperform their single-cell counterparts (Van den Berge et al, 2018). According to this comparison, the top-performing DE analysis tools are DESeq2 (Love et al, 2014) and EdgeR (Robinson et al, 2010) in combination with weights estimated by ZINB-wave .…”
Section: Differential Expression Testingmentioning
confidence: 99%
“…Note that we enforce identical basis functions between lineages, i.e., b k does not depend on l, as well as identical smoothing parameter g , in order to ensure that the smoothers are comparable across lineages. Importantly, the model of Equation (1) can accommodate zero-inflated counts typical for full-length scRNA-seq protocols by using observation-level (i.e., cell-level) weights obtained from the zero-inflated negative binomial (ZINB) approach of Van den Berge et al [2018] and Risso et al [2018a].…”
Section: Negative Binomial Generalized Additive Modelsmentioning
confidence: 99%
“…Zero inflation weights are estimated with the ZINB-WaVE method [Risso et al, 2018a], using the cluster labels and batch as covariates. Note that no other trajectory-based DE method can account for zero inflation or provide the range of tests available in tradeSeq; hence, we forgo a comparison with other methods aside from a ZINB-edgeR analysis [Van den Berge et al, 2018].…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the more common applications of RNA-seq data is estimating and testing for differences in gene expression between two groups. Many packages and techniques exist to perform this task [Robinson and Smyth, 2007b, Hardcastle and Kelly, 2010, Van De Wiel et al, 2012, Kharchenko et al, 2014, Law et al, 2014, Love et al, 2014, Finak et al, 2015, Guo et al, 2015, Nabavi et al, 2015, Delmans and Hemberg, 2016, Korthauer et al, 2016, Costa-Silva et al, 2017, Qiu et al, 2017, Miao et al, 2018, Van den Berge et al, 2018, Wang and Nabavi, 2018, Wang et al, 2019, and so developing approaches and software to compare these different software packages would be of great utility to the scientific community. Generating data from the two-group model is a special case of (1) and (2), where…”
Section: Application: Evaluating Differential Expression Analysismentioning
confidence: 99%